Dietary cranberry suppressed colonic inflammation and alleviated gut microbiota dysbiosis in dextran sodium sulfate-treated mice. Issue 10 (16th September 2019) - Cai, Xiaokun; Han, Yanhui; Gu, Min; Song, Mingyue; Wu, Xian; Li, Zhengze; Li, Fang; Goulette, Timothy; Xiao, Hang
Abstract : Oral administration of freeze-dried whole cranberry powder via diet inhibited colitis in dextran sodium sulfate-treated mice, which was associated with modification of gut microbiota. Abstract : Increased consumption of fruits may decrease the risk of chronic inflammatory diseases including inflammatory bowel disease (IBD). Gut microbiota dysbiosis plays an important etiological role in IBD. However, the mechanisms of action underlying the anti-inflammatory effects of dietary cranberry ( Vaccinium macrocarpon ) in the colon and its role on gut microbiota were unclear. In this study, we determined the anti-inflammatory efficacy of whole cranberry in a mouse model of dextran sodium sulfate (DSS)-induced colitis, as well as its effects on the structure of gut microbiota. The results showed that dietary cranberry significantly decreased the severity of colitis in DSS-treated mice, evidenced by increased colon length, and decreased disease activity and histologic score of colitis in DSS-treated mice compared to the positive control group ( p < 0.05). Moreover, the colonic levels of pro-inflammatory cytokine (IL-1β, IL-6 and TNF-α) were significantly reduced by cranberry supplementation ( p < 0.05). Analysis of the relative abundance of fecal microbiota in phylum and genus levels revealed that DSS treatment significantly altered the microbial structure of fecal microbiota in mice. α diversity was significantly decreased in the DSS group, compared to the healthy control group. But, cranberry treatment significantly improved DSS-induced decline in α-diversity. Moreover, cranberry treatment partially reversed the change of gut microbiota in colitic mice by increasing the abundance of potential beneficial bacteria, for example, Lactobacillus and Bifidobacterium, and decreasing the abundance of potential harmful bacteria, such as Sutterella and Bilophila. Overall, our results for the first time demonstrated that modification of gut microbiota by dietary whole cranberry might contribute to its inhibitory effects against the development of colitis in DSS-treated mice.